Exploring the Chemical Properties and Medicinal Applications of Tetramethylthiocycloheptyne Sulfoximine Used in Strain-Promoted Azide–Alkyne Cycloaddition Reactions - Matt Timmers; Andi Kipper; Raphael Frey; Stef Notermans; Maksym Voievudskyi; Claire Wilson; Nina Hentzen; Michael Ringle; Clara Bovino; Bernhard Stump; Cristianne J. F. Rijcken; Tina Vermonden; et al. (Pharmaceuticals, 2023)
The recently developed compound, tetramethylthiocycloheptyne sulfoximine (TMTHSI), has shown to be a promising strained alkyne for strain-promoted azide–alkyne cycloaddition (SPAAC), metal-free click chemistry. This research explores the properties of TMTHSI-based compounds via three aspects: (1) large-scale production, (2) unique stability in acidic conditions and its subsequent use in peptide synthesis, and (3) the functionalization of antibodies. Here, it is shown that (1) scale-up is achieved on a scale of up to 100 g. (2) TMTHSI is remarkably stable against TFA allowing for the site-specific functionalization of peptides on resin. Finally, (3) the functionalization of an antibody with a model payload is very efficient, with antibody conjugation demonstrating more beneficial features such as a high yield and limited hydrophobicity as compared to other alkyne reagent conjugates. These results illustrate the high potential of TMTHSI for diverse bioconjugation applications, with production already being GMP-compatible and a highly efficient conversion resulting in attractive costs of goods.